2015
DOI: 10.1159/000380897
|View full text |Cite
|
Sign up to set email alerts
|

Viruses, Other Pathogenic Microorganisms and Esophageal Cancer

Abstract: Background: Esophageal cancer (EC) is the eighth most prevalent malignant tumor and the sixth leading cause of cancer mortality throughout the world. Despite the technical developments in diagnosis and treatment, the 5-year survival rate is still low. The etiology of EC remains poorly understood; multiple risk factors may be involved and account for the great variation in EC incidence in different geographic regions. Summary: Infection with carcinogenetic pathogens has been proposed as a risk factor for EC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 76 publications
(112 reference statements)
0
36
0
2
Order By: Relevance
“…A potential role of HPV in the rise of esophageal AC was proposed recently. Multiple metaanalyses support the outcome of a higher HPV detection rate in regions associated with high risk for esophageal SCC compared to low-risk areas [9]. A meta-analysis showed that HPV16 and 18 can be detected in esophageal SCC.…”
Section: Introductionmentioning
confidence: 90%
“…A potential role of HPV in the rise of esophageal AC was proposed recently. Multiple metaanalyses support the outcome of a higher HPV detection rate in regions associated with high risk for esophageal SCC compared to low-risk areas [9]. A meta-analysis showed that HPV16 and 18 can be detected in esophageal SCC.…”
Section: Introductionmentioning
confidence: 90%
“…Among esophageal cancers, location (proximal and distal carcinoma) and histological subtype (adenocarcinoma and squamous cell carcinoma) can be separated [215][216][217][218][219], with differing etiology and prognosis. The upper gastrointestinal tract is most likely to show a specific response; this has been proven for viruses like human papilloma viruses [220] or hot and spicy food [221][222][223], cooking with wood and coal also are likely etiological agents [224,225]. In addition, genetic factors [226,227] contribute to the individual cancer risk, antibiotic treatment of H. pylori gastritis has caused a shift from squamous cell carcinoma to adenocarcinoma in esophageal cancers [218].…”
Section: Esophageal Cancermentioning
confidence: 99%
“…Multiple meta-analyses support the discovery of a higher HPV detection rate in regions associated with high risk for esophageal squamous cell carcinoma (ESCC), compared to low-risk areas. Additionally, a potential role of HPV in the rise of esophageal adenocarcinoma (EAC) was proposed recently; however, future studies are required (Xu et al, 2015). …”
Section: Elucidating the Host-microbiome Interactions And Cancer Devementioning
confidence: 99%